Contextual risk factors for the common mental disorders in Britain: a multilevel investigation of the effects of place. Issue 8 (25th July 2003) - Weich, S; Twigg, L; Holt, G; Lewis, G; Jones, K
Abstract : Study objective: To test hypotheses about associations between area level exposures and the prevalence of the most common mental disorders (CMD) in Britain. A statistically significant urban-rural gradient was predicted, but not a socioeconomic gradient, in the prevalence of CMD after adjusting for characteristics of individual respondents. The study tested the hypothesis that the effects of area level exposures would be greatest among those not in paid employment. Design: Cross sectional survey, analysed using multilevel logistic and linear regression. CMD were assessed using the General Health Questionnaire (GHQ). Electoral wards were characterised using the Carstairs index, the Office of National Statistics (ONS) Classification of Wards, and population density. Setting: England, Wales, and Scotland. Participants: Nearly 9000 adults aged 16–74 living in 4904 private households, nested in 642 electoral wards. Main results: Little evidence was found of statistically significant variance in the prevalence of CMD between wards, which ranged from 18.8% to 29.5% (variance 0.035, SE 0.026) (p=0.11). Associations between CMD and characteristics of wards, such as the Carstairs index, only reached statistical significance among those who were economically inactive (adjusted odds ratio for top v bottom Carstairs score quintile 1.58, 95% CI 1.08 to 2.31) (p<0.05). Conclusions: There may be multiple pathways linking socioeconomic inequalities and ill health. The effects of place of residence on mental health are greatest among those who are economically inactive and hence more likely to spend the time at home.